Endodontic sealers: Intratubular penetration and permeability to Enterococcus faecalis - Bortolini Maria Cecilia; Ferreira dos Santos Silvana; Habitante Sandra; Rodrigues Jane Rose; Vance Rodrigo; Jorge Antonio (Wolters Kluwer Medknow Publications, 2010)
Aim : Evaluate in vitro the intratubular penetration and permeability of endodontic sealers in teeth contaminated with Enterococcus faecalis. Materials and Methods : Human canines were filled with AHPlus ® , Endo CPM-sealer ® or EndoRez ® sealers. To evaluate permeability, the coronary portion of each tooth was contaminated with E. faecalis, then the apical portion was immersed in brain heart infusion (BHI) broth, and medium turbidity was observed for thirty days. Scanning electron microscope (SEM) was used to evaluate the intratubular penetration of each sealer at the cervical, middle, and apical thirds of the tooth. Results : Only one tooth from the Endo CPM-sealer ® group presented broth contamination. EndoRez ® showed increased intratubular penetration compared to AHPlus ® and Endo CPM-sealer ® . Conclusions : Endo CPM-sealer ® showed greater permeability to E. faecalis and EndoRez ® showed increased intratubular penetration.